HUBUNGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA DI POS KESEHATAN DESA BUKIT INDAH KOTAWARINGIN TIMUR - Fransiska Oktaviana; Sholaikhah Sulistyoningtyas; Suyani, Suyani (Journal of Innovation Research and Knowledge, 2025)
Anemia is one of the common health problems among pregnant women and can cause serious effects for both the mother and baby, such as premature delivery, low birth weight (LBW), and antepartum bleeding. The prevalence of anemia in pregnant women in Kotawaringin Timur increased from 37.1% in 2013 to 48.9% in 2018, and in 2022 there were 202 cases per 100,000 live births. One major cause of anemia is low adherence to taking iron (Fe) tablets, even though iron supplementation is an important effort to prevent anemia. This study aimed to determine the relationship between pregnant women’s adherence to consuming Fe tablets and the incidence of anemia. The study used a quantitative method with an analytical survey design and a cross-sectional approach. The population consisted of pregnant women who attended ANC (Antenatal Care) at the Health Post of Bukit Indah Village and joined the posyandu program. A total of 34 respondents, all in the third trimester of pregnancy, were selected using total sampling according to inclusion and exclusion criteria. The research instrument was the Medication Adherence Rating Scale (MARS-10), which had been tested for validity and reliability. The results showed that out of 12 respondents who were not adherent, 11 (32.4%) had anemia. Among the 14 respondents who were moderately adherent, 8 (23.5%) had anemia. Meanwhile, of the 8 respondents who were adherent, 7 (20.6%) did not have anemia. The chi-square test showed a p-value of 0.002 (p < 0.05), indicating a significant relationship between adherence to Fe tablet consumption and the incidence of anemia. It is recommended that pregnant women consistently take Fe tablets, have regular antenatal check-ups, and join health education to prevent anemia. Health services should improve education, monitoring, and distribution of Fe tablets through posyandu. Institutions are expected to support students in permits and guidance, while future researchers are advised to include more variables and larger samples for more representative results